Interaction of dicaproyl phosphatidylserine with recombinant factor VIII and its impact on immunogenicity - Purohit, Vivek S. (Springer-Verlag, 2006)
Replacement therapy with exogenous recombinant factor VIII (rFVIII) to control bleeding episodes results in the development of inhibitory antibodies in 15% to 30% of hemophilia A patients. The inhibitory antibodies are mainly directed against specific and universal immunodominant epitopes located in the C2 domain. Previously we have shown that complexation of O-phospho-L-serine (phosphatidylserine head group) with the phospholipid binding region of the C2 domain can lead to an overall reduction in the immunogenicity of rFVIII. Here, we have investigated the hypothesis that dicaproyl phosphatidylserine, a short-chain water-soluble phospholipid, can reduce the immunogenicity of rFVIII. Circular dichroism and fluorescence spectroscopy studies suggest that dicaproyl phosphatidyl-serine interacts with rFVIII, causing subtle changes in the tertiary and secondary structure of the protein. Sandwich enzyme-linked immunosorbent assay studies indicate that dicaproyl phosphatidylserine probably interacts with the phospholipid binding region of the C2 domain. The immunogenicity of FVIII-dicaproyl phosphatidylserine complexes prepared at concentrations above and below the critical micellar concentrations of the lipid were evaluated in hemophilia A mice. Our results suggest that micellar dicaproyl phosphatidylserine may be useful to reduce the immunogenicity of rFVIII preparations.